2005
DOI: 10.1093/ndt/gfh611
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and vascular calcification are independent predictors of left ventricular hypertrophy in chronic haemodialysis patients

Abstract: Extra-coronary atherosclerosis and vascular calcification are associated with LVH in HD patients. Whether the treatment of atherosclerosis or vascular calcification may cause regression of or even prevent LVH in HD patients remains to be seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 27 publications
3
33
2
3
Order By: Relevance
“…Calcifications at US were also common, affecting 36 (48%) of patients, a proportion comparable to the ones reported in previous studies, which varied from 50 to 64% [17][18][19] . Thirtythree out of our 36 patients with calcifications also exhibited increased IMT, whereas 10 patients with increased IMT did not have ultrasonographic calcifications.…”
Section: Discussionsupporting
confidence: 84%
“…Calcifications at US were also common, affecting 36 (48%) of patients, a proportion comparable to the ones reported in previous studies, which varied from 50 to 64% [17][18][19] . Thirtythree out of our 36 patients with calcifications also exhibited increased IMT, whereas 10 patients with increased IMT did not have ultrasonographic calcifications.…”
Section: Discussionsupporting
confidence: 84%
“…Elevated Ca ϫ PO 4 is a risk factor for arterial calcification (26,27). Previous studies demonstrated a potential role of PTH in promoting myocardial fibrosis (8), but our data showed no correlation between LVMI and PTH.…”
Section: Pre-hd Bp and Ca ϫ Po 4 : Increased Afterloadcontrasting
confidence: 77%
“…Persistently high AIs after hemodialysis might be explained by the presence of vascular structural damage (44). Vascular calcification has been associated with LVH (45,46), adverse cardiovascular outcomes, and mortality in patients on MHD (47,48).…”
Section: Discussionmentioning
confidence: 99%